Somatometryc's description by the youth Prykarpat'ya. - Malanyuk L.B (Kharkov National Pedagogical University, 2011)
hown features of morpho-functional status, individual changeability of anthropometric descriptions and degree of expressed of different components of mass of body depending on somatic type. Anthropometric researches conducted at 152 students by age 17-20 years which live in Precarpatian. In 83,4% of youths the set accordance of mass of body and circumference of thorax. In 6,1% of youths there is surplus of mass of body and in 10,5% the promoted density of body at the high values of muscular and fatty component. Among youths there is mainly pectoral (33,6 %) and muscular (27,0%) somatic type